KEWENANGAN NOTARIS DALAM PENJUALAN SAHAM PERSEROAN TERBATAS YANG PEMEGANG SAHAM MERUPAKAN PERUSAHAAN ASING - YENNY YENNY (PREMISE LAW JURNAL, 2016)
A notary must notarize an authentic notarial document in accordance with the provisions of the laws. Therefore, the transfer of the shares should be made in compliance with valid laws. The foreign companies under a joint venture agreement choosing the law of other country should obey the laws of Indonesia in the purchase of shares based on the principle of freedom of contract and it must not applied against the propriety, customs, and laws. In this case the law applied was the local law where the contract was made. The way of the purchase shares of foreign investment limited liability company catagorized as company types under established requirements must obtain permission from the authorities first. The authority of the notary in the purchase of shares of a foreign investment limited liability company of waarmerking general meeting of shareholders are managing the changes of equity and/or shareholders’ structure, making a deed of transfer of rights over shares in the form of authentic deed and deed under the hand and making a change to the data bank by filling Changes Format in the Legal Entity Administration System. Keywords: Notary Authority, Sale and Purchase Shares, Foreign Companies